2017
DOI: 10.2298/jmmb151206014p
|View full text |Cite
|
Sign up to set email alerts
|

Improving reducibility of iron ore pellets by optimization of physical parameters

Abstract: Reducibility of iron bearing material is an important property which represents its suitability of reduction in iron making furnaces. It has direct influence on improving productivity and lowering energy consumption in iron making process. The reducibility of iron ore pellets of a specific chemistry can be improved by the optimization of physical parameters such as induration temperature, improving size distribution of fines, improving apparent porosity etc. In this study, the reference pellet is prepared in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Investigators have tried to improve the reducibility by changing different parameters mainly through the change in chemistry and phase formation by different additives and fluxes. However, in our study reducibility index (RI) of hematite ore pellet has been increased with respect to the current level at the plant (Tata Steel, India) (Pal et al 2017b). However, other properties were maintained in the acceptable limit.…”
Section: Improving Reducibility Of Hematite Ore Pelletmentioning
confidence: 81%
See 2 more Smart Citations
“…Investigators have tried to improve the reducibility by changing different parameters mainly through the change in chemistry and phase formation by different additives and fluxes. However, in our study reducibility index (RI) of hematite ore pellet has been increased with respect to the current level at the plant (Tata Steel, India) (Pal et al 2017b). However, other properties were maintained in the acceptable limit.…”
Section: Improving Reducibility Of Hematite Ore Pelletmentioning
confidence: 81%
“…Optimum values of parameters have been found as induration temperature: 1275°C, lime stone size: below 350 mesh, coal size: below 350 mesh, for the iron ore Blaine fineness of 2855 cm 2 /g. The properties of pellets with these optimized values are shown in Table 7 (Pal et al 2017b). It is obvious from the table that reducibility index (RI) could be improved by 7-8% point and other properties viz.…”
Section: Improving Reducibility Of Hematite Ore Pelletmentioning
confidence: 99%
See 1 more Smart Citation
“…A method to weaken the unfavorable kinetic effect of the TRZ state change after decreasing the CSLR starting temperature on the indirect reduction is to improve the kinetic conditions of the indirect reduction, except temperature. In this study, the kinetic conditions of the indirect reduction are improved by increasing the reducibility of iron ore [18][19][20][21][22] or increasing the furnace top pressure. [23][24][25] Increasing the reducibility of iron ore to improve the kinetic conditions of indirect reduction is based on the principle that, according to the definition of iron ore reducibility, [26] the higher the reducibility of iron ore, the easier it is to lose the oxygen combined with iron in the iron ore by a gas-reducing agent, which implies a higher the reduction rate of the iron ore. For example, Yokoyama reported that when the ratio of carbon composite iron ore with high reducibility was 10%, the indirect reduction degree increased from 70.3% to 75.4%, and the CO utilization efficiency increased from 54.6% to 55.2% in a BF inner reaction simulator test.…”
Section: Introductionmentioning
confidence: 99%
“…Iron ore pellets as the indispensable burden of blast furnace show many benefits, such as high iron grade(> 63%TFe), high physical strength and uniform and size distribution, high and even porosity, less loss on ignition or volatiles, easy reducibility, and lower abrasion during transportation and use [1]. In recent years, under the pressure of energy saving and emission reduction in the iron and steel industry, the proportion of pellets charging into the blast furnace increase, and higher requirements were put forward for the quality and metallurgical performances of the pellets [2][3][4][5][6][7]. By increasing the content of MgO in iron ore pellets, not only the metallurgical performances of pellets are improved, but also the MgO content in sinter (another burden of blast furnace) decrease, because the excess MgO in sinter causes many negative effects such as the sintering rate, the fuel rate, and the sinter strength and reducibility deteriorate [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%